2010
DOI: 10.1038/jid.2009.221
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Microbiology: New Dimensions for Cutaneous Biology and Wound Healing

Abstract: The role of bacteria in the pathogenesis of chronic, nonhealing wounds is unclear. All wounds are colonized with bacteria, but differentiating colonizers from invading organisms is difficult, if not impossible, at the present time. Furthermore, robust new molecular genomic techniques have shown that only 1% of bacteria can be grown in culture; anaerobes are especially difficult to identify using standard culture methods. Recent studies utilizing microbial genomic methods have demonstrated that chronic wounds a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
99
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(106 citation statements)
references
References 99 publications
(124 reference statements)
3
99
2
Order By: Relevance
“…B. multivorans, B. cenocepacia, P. aeruginosa, and S. aureus often infect cystic fibrosis patients and were consequently evaluated in SCFMM medium mimicking the conditions found in the cystic fibrosis lung (13,29,35). Both P. aeruginosa and S. aureus cause soft tissue infections (23,25), and for this reason the biofilm susceptibility of these species was evaluated in two in vitro wound models and on RHE (36,40). QSI targeting different QS systems and different classes of antibiotics were included, the latter in clinically relevant concentrations (8,12).…”
Section: Discussionmentioning
confidence: 99%
“…B. multivorans, B. cenocepacia, P. aeruginosa, and S. aureus often infect cystic fibrosis patients and were consequently evaluated in SCFMM medium mimicking the conditions found in the cystic fibrosis lung (13,29,35). Both P. aeruginosa and S. aureus cause soft tissue infections (23,25), and for this reason the biofilm susceptibility of these species was evaluated in two in vitro wound models and on RHE (36,40). QSI targeting different QS systems and different classes of antibiotics were included, the latter in clinically relevant concentrations (8,12).…”
Section: Discussionmentioning
confidence: 99%
“…Our results are in coincidence with results from previous studies. [65][66][67][68][69] Martin et al 20 found that the presence of one microorganism generates an appropriate environment for other pathogenic microorganisms, which are able to colonize the respective niche, so 2 or more pathogenic microorganisms could synergically interact to cause disease.…”
Section: Incidence Of Monomicrobial and Polymicrobial Infectionsmentioning
confidence: 99%
“…Polysaccharide biofilm is an important barrier to microbial consortia, enabling their escape from host immunity and confers increased tolerance to antimicrobials when compared with monomicrobial infections. 19,20 Moreover, the increase in MDR is due to the strong antibiotic selective pressure from the clinical and environmental origin. The most common etiological bacteria attributed to chronic burn wound infections are Pseudomonas aeruginosa, Staphylococcus aureus, Streptococcus spp., Klebsiella spp., Enterococcus spp., and Escherichia coli.…”
Section: Introductionmentioning
confidence: 99%
“…Genomic tools such as nucleic acid amplification, DNA sequencing, and the development of microbial ribosomal clone libraries have greatly expanded our view of wound microbial flora. As the genomic tools used to obtain the molecular signature of complex microbiomes are relatively new, more information is required to establish which microbes are deleterious and impair healing, which are benign colonizers, and which may even facilitate healing processes (22). In spite of the lack of understanding of the microbial composition of chronic wounds, topical and systemic antibacterial agents are used liberally in wound care, possibly promoting the development of resistant bacterial strains and/or killing potentially beneficial bacteria.…”
mentioning
confidence: 99%